(untitled) (JS (JURNAL SEKOLAH), 2022)
Abstract: Optimization of Student Learning Outcomes Through Peer Teaching Based on Audio-Visual Media for Vocational Students. This study aims to improve students’ cultural arts learning outcomes through peer tutors. This research uses classroom action research adopted from the Kemmis and McTaggart model. Four stages of research have been used in two cycles of this research. A total of 36 students of class X TKJB were involved as research respondents. Student learning outcomes are assessed using performance techniques through audio-visual recordings. Data on student learning outcomes were analyzed using the percentage technique. After learning two cycles, the average student learning outcomes and classical completeness have increased. So, it can be concluded that peer tutoring methods can improve student learning outcomes. This implies that peer tutoring methods can be applied to other subject matter. Keywords: Learning Outcomes; Peer Teaching; Audio-Visual Media; CAR Abstrak: Optimalisasi Hasil Belajar Siswa Melalui Tutor Sebaya Berbasis Media Audio-Visual pada Siswa Kejuruan. Penelitian ini bertujuan untuk meningkatkan hasil belajar seni budaya siswa melalui tutor sebaya. Penelitian ini menggunakan jenis penelitian Tindakan kelas yang diadopsi dari model Kemmis dan McTaggart. Empat tahap penelitian telah digunakan dalam dua siklus penelitian ini. Sebanyak 36 orang siswa kelas X TKJB dilibatkan sebagai responden penelitian. Hasil belajar siswa dinilai menggunakan Teknik unjuk kerja melalui rekaman audio visual. Data hasil belajar siswa dianalisis menggunakan teknik persentase. Nilai rata-rata hasil belajar dan ketuntasan klasikal siswa meningkat setelah dua siklus pembelajaran. Akibatnya, dapat dinyatakan bahwa menggunakan pendekatan tutor sebaya dapat membantu siswa belajar lebih efektif. Ini memiliki konsekuensi untuk metode tutor sebaya dapat digunakan dalam berbagai mata pelajaran. Kata kunci: Hasil Belajar; Tutor Sebaya; Media Audio-Visual; PTK